1992
DOI: 10.1093/jmedent/29.4.669
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of Tick-Borne Infections at Fort Chaffee, Arkansas: Rickettsiae and Borrelia burgdorferi in Ixodid Ticks

Abstract: Human intrusion into pristine habitats increases the likelihood of acquiring infectious agents from potentially infective ticks. As part of a larger human serological investigation into tick-borne illnesses, 3,000 ixodid ticks were collected during May, August, and November 1990 at Fort Chaffee, Arkansas. Ticks were examined to determine whether they harbor rickettsiae, ehrlichiae, and Borrelia burgdorferi, and to assess relationship to human exposure to tick-borne infections at Fort Chaffee, Ark. The overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…It is known that the ticks harbor the spotted fever group of rickettsiae (4.8%) more often than Francisella tularensis (1.8%), E chaffeensis (0.3%), or Borrelia burgdorferi (0.1%). 5,6 The low numbers of reported infections in Arkansas may be attributable to the low number of infected ticks or the lack of adequate identification and reporting of this illness. Comparing RMSF, tularemia, and ehrlichiosis, we recognize the fact that reports from our institution comprise approximately 39% of the cases of RMSF, 38% of the cases of tularemia, but all of the ehrlichia cases in children Ͻ15 years of age (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the ticks harbor the spotted fever group of rickettsiae (4.8%) more often than Francisella tularensis (1.8%), E chaffeensis (0.3%), or Borrelia burgdorferi (0.1%). 5,6 The low numbers of reported infections in Arkansas may be attributable to the low number of infected ticks or the lack of adequate identification and reporting of this illness. Comparing RMSF, tularemia, and ehrlichiosis, we recognize the fact that reports from our institution comprise approximately 39% of the cases of RMSF, 38% of the cases of tularemia, but all of the ehrlichia cases in children Ͻ15 years of age (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Tick-transmitted infection is an occupational health threat to military personnel (10,24,31). Effective arthropod repellents are available through the military supply system and are actively promulgated (Armed Forces Pest Management Board, technical guide 36 [http://www.afpmb.org/coweb/guidance targets/ppms/TG36/TG36.htm]); nevertheless, compliance is inadequate and many soldiers in the field experience tick bites (8).…”
mentioning
confidence: 99%
“…Ticks bit 75% of the personnel who participated in the training exercise, and one-half of these personnel were seropositive for Rickettsia rickettsii, which shares SFGR antigens with R. amblyommii. In examining more than 3,000 ticks at Fort Chaffee, Arkansas, during May, August, and November 1990, Kardatzke et al 86 found that 4.8% were positive for SFGR and 0.3% were positive for ehrlichiae. Stromdahl et al 82 80 Another SFGR, Rickettsia parkeri, was previously observed in the Gulf Coast tick, Amblyomma maculatum, and was considered to be nonpathogenic.…”
Section: Us Military Significancementioning
confidence: 99%